EXPERIENCE OF CONTROL OF THE QUALITY AND NONMETALLICS COMPOSITION IN HIGH-CARBON STEEL - A. S. Zazian (Литьë и металлургия)
The following technological methods have been applied for control the composition and quantity of non-metallics in rolled wire of test meltings: work on “pure” burden, application of materials with minimal content of impurities, non-slaggy regime, fettling of steel- bowls.